PERAN MEDIASI SEBAGAI UPAYA PERDAMAIAN DALAM MENGATASI PERCERAIAN OLEG PENGADILAN AGAMA - Melati, Resta (Causa: Jurnal Hukum dan Kewarganegaraan, 2023)
Marriage is a human need in order to continue offspring. This is regulated in article 1 of Law no. 1 of 1974 concerning Marriage. Marriage has the aim of building a household or family that is sakinah, mawadah and warahmah. However, not all marriages can run well, because household problems often occur that cannot be resolved until the end result is divorce. Divorce cases will initially be resolved through mediation, or involve the role of a third party (mediator) in resolving problems that occur between the first party and the second party. Divorce settlement through mediation has benefits, because the parties can reach a decision that they feel is fair to them. Mediation also aims to be an effort to reunite the relationship between husband and wife who have been registered with the religious court for the divorce process, so that the divorce can be annulled. Mediation carried out in religious courts is regulated in PERMA No. 1 of 2008 concerning mediation and PERMA No. 1 of 2016 concerning Mediation Procedures in Court. At the mediation stage in religious courts, there are three stages, including the pre-mediation stage, the mediation implementation stage, and the final stage of implementing the mediation results. These three stages must be carried out so that the mediation runs smoothly and for both parties having a dispute to get a satisfactory final result.